Influence of situational variables on the U’18 soccer performance analysis (Análisis de la influencia de las variables situacionales en el rendimiento en futbol U’18) - Pablo Caballero; Javier Garcia Rubio; Sergio José Ibáñez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Team sports performance analysis usually uses samples of high performance teams and athletes. Those studies, although useful to trainers and players, are hardly applicable on different contexts. The goal of this study was to analyze the effects of the situational variables on the final score and competition in youth soccer. To achieve this, all games from a Spanish regional youth soccer league (n=132) were analyzed. Linear regressions were used to check the influence of situational variables (score difference; final league standings; match location; scoring first; cards; substitutions; quality of opponent and field surface) on the outcome of the game, final team standings and game location. Results show the importance that the match location, scoring first, rival team quality, substitutions and cards have on the match’s outcome, meanwhile the linear regression highlights the effect of scoring first, rival team quality, and substitutions on the final team standings.